Strategies and Determinants of Knowledge Management and Sharing in Healthcare Organizations: A Narrative Review - Leila Banifatemeh; Nadjla Hariri; Mostafa Farahbakhsh (Taṣvīr-i salāmat)
Background. Effective and efficient sharing of knowledge in health care can lead to the clarification of health data and dissemination of up-to-date health information among employees, decision-makers, and other stakeholders, thereby improving the probability of occurrence of desirable health outcomes. The current study aimed to identify the determinants of effective knowledge management and sharing in healthcare. Methods. This study was conducted to identify the facilitators and barriers of knowledge sharing in healthcare and also identify successful strategies in this field using the approach of review studies in 2023. A thorough literature review was conducted using relevant keywords in PubMed, Scopus, and SID databases and the Google Scholar search engine. Data extraction was done by two researchers using the data extraction table. The content analysis method was used to analyze the data. Results. Reviewing 21 studies revealed 176 determinants of knowledge management and sharing in healthcare organizations. Among the determining factors, 96 were facilitators, and 80 were barriers to knowledge sharing. After removing duplicate factors and merging similar cases, 54 facilitators and 55 barriers were obtained uniquely. The determining factors were classified into four categories: organizational factors, infrastructure factors, individual factors, and factors related to the information system. Also, 35 effective strategies for knowledge management in healthcare organizations were identified, the most important of which was related to the empowerment of managers in information technology (IT). Conclusion. The success of knowledge sharing in healthcare requires a strong IT infrastructure, supportive leadership, an organizational culture that governs knowledge development, commitment and cooperation among healthcare team members, and effective knowledge management.